Suicidal ideation and suicide attempts in healthcare professionals during the COVID-19 pandemic: A systematic review - García-Iglesias, Juan Jesús; Gómez-Salgado, Juan; Fernández-Carrasco, Francisco Javier; Rodríguez-Díaz, Luciano; Vázquez-Lara, Juana María; Prieto-Callejero, Blanca; Allande-Cussó, Regina (Frontiers in Public Health, 2022)
Background COVID-19 has caused a series of economic, social, personal, and occupational consequences that may affect the mental health of healthcare workers (HCWs), with the consequent risk of developing suicidal ideation and behaviors. Objectives The aim of this study was to identify the main risk factors that may predispose HCWs to suicidal ideation and suicide attempts during the COVID-19 pandemic. Methods A systematic review of studies published between January 2020 and August 2022 was conducted following the PRISMA guidelines in the following electronic databases: Pubmed, Scopus, Web of Science, CINAHL, and PsycINFO. Methodological quality was assessed using the critical appraisal tools for non-randomized studies of the Joanna Briggs Institute (JBI). The followed protocol is listed in the International Prospective Register of Systematic Reviews (PROSPERO) with code CRD42022340732. Results A total of 34 studies were included in this review. There are a number of underlying factors such as higher rates of depression, anxiety, pre-pandemic lifetime mental disorders or previous lifetime suicide attempt, living alone, having problems with alcohol and/or other drugs, etc. that favor the emergence of suicidal tendencies and ideation in times of COVID-19. Similarly, the pandemic may have precipitated a series of factors such as economic concerns, assessing one's working conditions as poor, having family members or friends infected, changes in services or functions, and feeling discriminated against or stigmatized by society. Other factors such as age, sex, or type of healthcare worker show differences between studies. Conclusion Organizations should ensure the adoption of strategies and programmes for early detection of suicides as well as increased attention to the mental health of professions with a high workload. Systematic review registration PROSPERO, identifier CRD42022340732.